Perlukah Sanksi Pidana Ekonomi Syariah di Aceh? - Bawono, Royan; Dayyan, Muhammad; Faisal, Faisal (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
Sharia economic crimes have not been regulated in the form of legal norms that require criminal sanctions. In fact, the crime exists and often causes victims to be in debt, which leads to apostasy. This article is classified as literature research with a qualitative approach. The methodology used is the study of normative legal analysis. The results showed that a sharia economic criminal qanun is needed that regulates criminal sanctions for perpetrators of sharia economic cultivation in Aceh based on three foundations. First, the philosophical principle of economics in Aceh, which is in line with Islamic law, is the Islamic view of life of the Acehnese people, referring to the Qur'an and Hadith. Second, juridically, there is a formal legal basis for making the Aceh Qanun concerning Sharia Economic Crimes, namely Law No. 11 of 2006 concerning the Government of Aceh, Aceh Qanun No. 8 of 2014 concerning the Principles of Islamic Sharia, and Aceh Qanun No. 11 of 2018 concerning Sharia Financial Institutions. Third, sociologically, it is necessary to meet the legal needs of the community with the development of empirical facts that there are still elements of usury, gharar, and others in economic activities that disturb the people of Aceh.